Accessibility of Higher Education for Students with Disabilities - Kurbangaleyeva E.S; Veretennikov D.N (Moscow State University of Psychology and Education, 2017)
The Autonomous Non-Commercial Organization "Minority Report" Research Center carried out a complex all-Russian monitoring of accessibility of higher education for students with disabilities in 1/3 of state universities (165 universities in 51 regions). The authors explored the issue from the point of view of organizations offering services in higher education (universities) as well as from the point of view of their customers (disabled students and their parents) and completed the picture with the data obtained through monitoring and participant observation; this enabled the authors to reveal the main problems that students with disabilities experience in getting higher education - in the stages of career guidance, university admission, studying at university and further employment. For instance, the authors point out to the legal restriction 'one university - one profession' referring to admission quotas for students with disabilities; problems with getting documents required for university application; low accessibility of educational environment and insufficient supply of special teaching devices; low accessibility of university websites etc. The authors propose the following specific measures for raising the accessibility of higher education for the disabled: introducing changes to legal acts restricting the opportunities of the disabled in higher education; changing the practices in organizations responsible for medical and social assessment in how they provide documents required for university application; expanding the services offered by resource and training centers; introducing a unified standard for university websites in sections referring to disability services, etc. This project was supported by state grant funds, Executive Order of the President of the Russian Federation issued on April 01, 2015 #79-рп, and on the basis of the contest carried out by the All-Russian Non-Governmental Organization «Liga Zdorovya Natsii».